Denying the Spoils of War The Politics of Invasion and Non-recognition - O'Mahoney, Joseph (Edinburgh University Press, 2018)
Joseph O'Mahoney systematically analyses 21 case studies - including the Manchurian Crisis, the Turkish invasion of Cyprus and Russia's annexation of Crimea - to explore why so many states have adopted a policy of non-recognition of the spoils of war.